Construction of Functionalized Carbocycles Having Contiguous Tertiary Carbinol and All‐Carbon Stereogenic Centers. Issue 12 (1st March 2013) - Reddy, Chennakesava; Babu, Srinivasarao Arulananda; Aslam, Nayyar Ahmad; Rajkumar, Vadla
Abstract: A highly stereoselective protocol is reported for customizing functionalized carbocyclic building blocks (β‐hydroxy esters) and bicyclic lactones with a stereoarray that contains contiguous tertiary carbinol and all‐carbon stereocenters. The efficient asymmetric induction and diastereofacial selective addition of allyl and propargyl indiums to hindered α, α‐disubstituted cycloalkanones is presented. The stereochemistry of representative products was unequivocally established from single‐crystal X‐ray crystal structure analyses, and a plausible reaction pathway was proposed to support the high diastereofacial selectivity. Abstract : The indium‐mediated installation of a stereoarray that consists of contiguous tertiary carbinol and all‐carbon stereocenters in functionalized carbocyclic building blocks and bicyclic lactones is presented. The absolute stereochemistry of the products was established for the highly diastereofacial selective addition of allyl and propargyl indiums to α‐alkyl‐α‐(ethoxycarbonyl)cycloalkanones.